Associations of prenatal exposures to low levels of Polybrominated Diphenyl Ether (PBDE) with thyroid hormones in cord plasma and neurobehavioral development in children at 2 and 4 years. (October 2019) - Ji, Honglei; Liang, Hong; Wang, Ziliang; Miao, Maohua; Wang, Xin; Zhang, Xiaotian; Wen, Sheng; Chen, Aimin; Sun, Xiaowei; Yuan, Wei
Abstract: Background: Neurotoxic effects of Polybrominated Diphenyl Ethers (PBDEs) at low levels have not been well studied in human population, and whether the associations can be explained by thyroid hormones (THs) remains unclear. Objectives: We examined the associations of prenatal PBDE exposures with THs in cord plasma and neurobehavior of children at 2 and 4 years among general population in China. Methods: Participants were mother-child pairs in the Shanghai-Minhang Birth Cohort Study. Nine PBDE congeners and THs (thyroid stimulating hormone, total thyroxine, free thyroxine, total triiodothyronine, and free triiodothyronine) were determined in cord plasma. Child Behavior Checklist (CBCL/1.5-5) were completed by caregivers to assess children's neurobehavioral development at 2 and 4 years. In the final analyses, 199 and 307 mother-child pairs at 2 and 4 years were included to examine associations of PBDEs with CBCL scores using Pearson-scale-adjusted Poisson regressions, and 339 subjects were included in linear regression models to investigate the associations between PBDEs and THs. Results: BDE-47 had the highest detection rate of 83.82% with the median concentration of 0.19 ng/g lipid, followed by BDE-28, −99, −100 and −153 with detection rates nearly 50%. We found positive associations between prenatal PBDE concentrations and children's neurobehavior, including Somatic Complaints, Withdrawn, Sleep Problems and Internalizing Problems in girls, and Somatic Complaints and Attention Problems in boys. We also observed inverse associations of the sum of BDE-47, −28, −99, −100 and −153 with THs. However, by adding THs to the models examining associations between PBDEs and CBCL, the main results didn't measurably change. Conclusions: This study adds new knowledge that prenatal PBDEs at low levels may be related to long-lasting behavioral abnormalities in children and reduced THs in cord plasma. However, the hypothesis that the neurotoxic impact of PBDEs may be explained by alterations in cord THs was not supported. Highlights: Prenatal PBDEs at low levels may be related to long-lasting behavioral abnormalities in children. PBDE concentrations in cord plasma were inversely associated with cord thyroid hormone levels. The hypothesis that the neurotoxic impact of PBDEs may be explained by alterations in cord thyroid hormones was not supported.